Viral circular RNA–encoded protein, ceVP28, divulges an antiviral response in invertebrates - Sirawich Limkul; Tannatorn Phiwthong; Supitcha Wanvimonsuk; Tuangrak Seabkongseng; Phirom Aunkam; Phattarunda Jaree; Waruntorn Luangtrakul; Kanjana Mahanil; Kamonluck Teamtisong; Panlada Tittabutr; Neung Teaumroong; Peter Sarnow; et al. (Proceedings of the National Academy of Sciences, 2025)
Invertebrates mostly use innate immunity to counteract pathogenic infections. In this study, shrimp was used as a model organism to explore the functions of circular RNAs (circRNAs) derived from white spot syndrome virus (WSSV). We identified four viral circRNAs, termed circWSSV147, circWSSV326, circWSSV458, and circVP28, from transcriptomic data of WSSV-infected shrimp. CircVP28, which contains an internal ribosome entry site, was further characterized to determine its potential as a template for protein translation. We observed the presence of a truncated, circRNA-encoded VP28 (ceVP28) in infected shrimp. Both ceVP28 and its parental counterpart, VP28, share the same host cell binding partner Rab7, which is a host receptor for WSSV. Coadministration of recombinant ceVP28 protein and WSSV to penaeid shrimps reduced both viral copy numbers and mortality upon WSSV challenges. These findings uncovered a host defense mechanism by which a protein encoded by a viral circRNA modulates virus–receptor interactions, resulting in blocking of viral entry.